Relationship between renal volume calculated by using multislice computed tomography and glomerular filtration rate calculated by using the cockcroft-gault and modification of diet in renal disease equations in living kidney donors - Adibi, Atoosa; Murtadawi, Mujan; Shayganfar, Azin; Kamal, Sima; Azad, Roya; Aalinezhad, Mardiah (Saudi journal of kidney diseases and transplantation, 2016)
It is essential to ascertain the state of health and renal function of potential kidney donors before organ removal. In this regard, one of the primary steps is to estimate the donor’s glomerular filtration rate (GFR). For this purpose, the modification of diet in renal disease (MDRD) and the Cockcroft–Gault (CG) formulas has been used. However, these two formulas produce different results and finding new techniques with greater accuracy is required. Measuring the renal volume from computed tomography (CT) scan may be a valuable index to assess the renal function. This study was conducted to investigate the correlation between renal volume and the GFR values in potential living kidney donors referred to the multislice imaging center at Alzahra Hospital during 2014. The study comprised 66 subjects whose GFR was calculated using the two aforementioned formulas. Their kidney volumes were measured by using 64-slice CT angiography and the correlation between renal volume and GFR values were analyzed using the Statistical Package for the Social Science software. There was no correlation between the volume of the left and right kidneys and the MDRD-based estimates of GFR (P = 0.772, r = 0.036, P = 0.251, r = 0.143, respectively). A direct linear correlation was found between the volume of the left and right kidneys and the CG-based GFR values (P = 0.001, r = 0.397, P <0.001, r = 0.465, respectively). The kidney volume derived from multislice CT scan can help predict the GFR value in kidney donors with normal renal function. The limitations of our study include the small sample size and the medium resolution of 64-slice multislice scanners. Further studies with larger sample size and using higher resolution scanners are warranted to determine the accuracy of this method in potential kidney donors.